Implementasi Pasal 153 Ayat 1 Huruf A Undang-Undang Nomor 13 Tahun 2003 Tentang Larangan PHK - Marhusor Siahaan, Alpiner; Hutasoit, Natanael Yosua; Yehezkiel, Fransiscus; Andini, Andini; Sihombing, Chandra Alexander (Journal of Industrial Relations Studies, 2025)
Cases of employment termination (layoffs) involving workers who are ill continue to occur, despite being prohibited under Article 153 paragraph (1) letter g of Law Number 13 of 2003 concerning Manpower. One such case took place at PT Sumber Batu Cakrawala (SBC) in Katibung, South Lampung, where the company allegedly dismissed a sick employee without following the proper legal procedures. This study aims to examine the implementation of the relevant legal provisions at PT SBC and analyze the action from the perspective of Islamic law. Using a normative juridical method with a literature study approach, the research found that the dismissal violated positive law and contradicted the principles of justice in Islam. Therefore, stronger supervision of labor law enforcement and the integration of Islamic justice values are needed to create a fair, humane, and ethical employment system